PENGARUH KARAKTER EKSEKUTIF, KOMPENSASI EKSEKUTIF, GENDER DIVERSITY, KONEKSI POLITIK, DEBT TO EQUITY TERHADAP PENGHINDARAN PAJAK DAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING - Muhammad Alfian Putra; Andreas Andreas; Nasrizal Nasrizal (Jurnal Ekonomi, 2018)
This study aims to examine the effect of executive character, executive compensation, gender diversity, political connections and debt to equity ratio on tax avoidance and earnings management as intervening variables. The target population of this study is manufacturing companies listed on the Indonesia Stock Exchange in the observation period of 2012 - 2016. The method in selecting research samples used purposive sampling as many as 40 sample companies. Data analysis methods used path analysis technique. Based on the estimation results of WarpPLS 5.0, path coefficient shows that executive character, gender diversity, and debt to equity ratio affect earnings management, while executive compensation and political connections have no effect on earnings management. Earnings management, executive character, executive compensation, gender diversity, and debt to equity ratio affect tax avoidance, while political connections do not affect tax avoidance. It is proven that earnings management mediates executive character and debt to equity ratio to tax avoidance, while earnings management is not proven to mediate executive compensation, gender diversity and political connections to tax avoidance.